(-)-Sativan Inhibits Tumor Development and Regulates miR-200c/PD-L1 in Triple Negative Breast Cancer Cells - Peng, Fu; Xiong, Liang; Peng, Cheng (Frontiers in Pharmacology, 2020)
Epithelial-to-mesenchymal transition (EMT) in cancer cells could convert epithelial-like cells to mesenchymal-like cells, resulting in the increasing capacity of migration and invasion of cancer cells, and is an essential step of triple negative breast cancer (TNBC) development. Recent reports exert that these EMT-activated TNBC cells are more resistant to immune attacks, with high levels of programmed death ligand1 (PD-L1). Hence, it is worthwhile to find the effective approach to inhibit EMT-activated TNBC cells. (-)-Sativan (SA) is a naturally isolated isoflavane and could be isolated from Spatholobus suberectus, a common traditional Chinese medicine used for breast cancer treatment. It was the first time that SA exerted anti-cancer effects on breast cancer cells according to our study. In this study, SA displayed a significant inhibitory effect on TNBC cells proliferation by inducing apoptosis. SA increased Bax expression, and decreased Bcl-2 protein levels. SA inhibited cell migration and invasion of MDA-MB-231 and BT-549 cells. SA could decrease N-cadherin, Snail, Vimentin and PD-L1 expression. SA increased miR-200c expression, and decreased PD-L1 expression. Luciferase assay showed that miR-200c directly targeted PD-L1. SA promoted tumor cell susceptibility to CTL-mediated lysis. Further study confirmed that SA could inhibit PD-L1 expression and EMT by up-regulating miR-200c. In vivo results displayed that SA could also inhibit tumor volumes and weights. These findings indicated that SA exerted an inhibitory effect on TNBC cell proliferation, migration, invasion and tumor growth, and partly provide evidence for the anti-breast cancer effect of Spatholobus suberectus Dunn in TNBC therapy.